REGULARITIES OF FORMATION OF THE REGION’S RECREATIONAL POTENTIAL - Melniichuk, Mykhailo; Petlin, Valerii (European Science, 2025)
Laws are summarized as theoretical basis for the formation of recreational potential of the region. The structure and dependence of the organization of recreational potential on the features of its geographical environment is shown. The experience of dif